EFFECT OF TEACHER PERSONALITY IN EDUCATIONAL PROCESS - Kushwaha, Anil Kumar Singh; Shelly (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Teacher’s personality is an important factor in terms of teaching-learning, classroom management and students’ motivation and participation. The aim of this study was to investigate how different aspects of teacher’s personality affect the relationship between students’ learning and motivation. In this study, we reviewed various research papers and collected information regarding the direct and indirect effects of teacher personality in them. Our study revealed that teacher’s personality is effective in relation to motivation, learning and student-teacher relationship with some important traits. Therefore, personality analysis of teachers should be seen as an important research topic that enhances cognition in the field of teaching and learning and their relationships. Recent studies have focused on teacher’s personality in basic education learning. This study provides a pooled analysis to understand the relationship of teachers’ personality traits and important outcomes such as discipline practices by teachers towards their students, learning effectiveness, job satisfaction and burnout. This study reviews five different studies that focus on teachers’ personality. In this study, various methods such as meta-analysis and accountability assessment have been used to analyse the personality traits of teachers. The results of this study indicate the importance of personality traits of teachers as they relate to their teaching effectiveness, student-teacher relationship and education outcomes.